State-political and people's collaborationism in Europe in the Second World War period - Kazantsev Yuriy (E3S Web of Conferences, 2020)
Impedance coatings of cylindrical bodies’ synthesis in order to The authors of the article made an attempt to reveal the main causes and motives of mass collaboration in European countries during the Second World War. Mentally, European man has recognized himself as part of a single space for centuries, under one-man rule: the Roman Empire, the Empire of Charlemagne, and the Holy Roman Empire. The imperial idea initially suggested the European peoples’ unification under the auspices of a strong center. The second component of the European mentality was built on the idea of Eurocentrism, proclaiming the superiority of European nations over others, and Western European civilization over the rest of the world. The ruling elite of the German Empire made plans to create "Middle Europe", proclaimed in 1871, which incorporated the economic union of Germany, Austria-Hungary, Belgium, Holland, Denmark, Poland and trimmed France. In 1923, a new idea was published in the manifesto of an Austrian political scientist, Kudenhove-Kalergi - "pan-Europe." The author meant a new, political, single space, spoke about pan-Europe. At the beginning of 1925 the United States of Europe appeared as a more recent idea. These were concrete steps towards creating a united Europe. On the eve of the war years and during that period, leaders and population of European countries were increasingly inclined to take joint actions with Hitler to create a new European device to be able to oppose communist expansion. Mentally, Europe was ready to create a strong core that organized the European space.